Two-Layered Sharīʿa: A Shiʿi Distinction Between Farāʾiḍ and Sunan Laws - Rajani, Kumail (Islamic law and society, 2025)
This article examines the historical background of the distinction between farāʾiḍ and sunan laws in early Shiʿi hadith literature. Unlike the farāʾiḍ, which are understood as laws that have been decreed by God, sunan are characterized as laws stipulated by the Prophet without any direct divine intervention. The Prophet is entrusted, Shiʿi hadiths suggest, with the authority of legislative delegation (tafwīḍ al-tashrīʿ). In this article I will: (1) analyze hadiths concerning the Prophet’s legislative authority and legal stipulations; (2) examine the emergence of this nomenclature within the intellectual milieu of 2nd/8th century Iraq; and (3) explore the role of intra-Shiʿi debates on the transcendent status of the Imams and their contribution to the discourse on a two-layered sharīʿa, a framework that, within the Shiʿi legal tradition, facilitates the extension of legislative authority to the Imams in the absence of the Prophet.